Speech Acts in Intercultural Communication: A Cross-Cultural Comparison of Politeness Strategies - Keith, Britney (International Journal of Linguistics, 2025)
Abstract Purpose: The general objective of this study was to analyze how different cultures use speech acts and politeness strategies in everyday communication. Methodology: The study adopted a desktop research methodology. The study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to speech acts in intercultural communication. Preliminary empirical review revealed that social media significantly transformed politeness strategies in intercultural communication, shifting towards greater informality and directness compared to traditional face-to-face interactions. Unique Contribution to Theory, Practice and Policy: The study recommended expanding politeness theory to include digital communication contexts, as social media’s informality challenged traditional models of politeness.